1988
DOI: 10.1159/000181072
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Treatment with Growth Hormone-Releasing Hormone for Short Stature

Abstract: In the present study we report the effects of therapy with growth hormone-releasing factor (1–29)NH2 (GRF) on growth rate, plasma levels of insulin growth factor I (IGF-I) and growth hormone (GH) secretion in 11 children who were selected solely on the basis of their short stature and normal GH secretion on standard provocative tests. All children received GRF for 6 months (5 µg/kg body weight subcutaneously) each evening. The 24-hour GH secretory profile was studied before and after 6 months of treatment. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Short-term therapy with GH over one year with GH in short children without GH insufficiency has been shown to increase height velocity in children who are growing slowly (Albertsson-Wikland, 1988, Wit et al, 1989 or 'normally' (Hindmarsh & Brook, 1987). As in the present study, the growth response to both GH (Albertsson-Wikland, 1988) and GHRH (Hernandez et al, 1988) in children who are not GH insufficient appears to be dependent on the pretreatment height velocity. Unlike growth hormone, however, we administered twice-daily injections, as we have previously shown this regime to be effective (Ross et al, 1987) and other studies have shown waning of the growth response (Rochiccioli et al, 1987) on once-daily injection.…”
Section: Discussionsupporting
confidence: 68%
“…Short-term therapy with GH over one year with GH in short children without GH insufficiency has been shown to increase height velocity in children who are growing slowly (Albertsson-Wikland, 1988, Wit et al, 1989 or 'normally' (Hindmarsh & Brook, 1987). As in the present study, the growth response to both GH (Albertsson-Wikland, 1988) and GHRH (Hernandez et al, 1988) in children who are not GH insufficient appears to be dependent on the pretreatment height velocity. Unlike growth hormone, however, we administered twice-daily injections, as we have previously shown this regime to be effective (Ross et al, 1987) and other studies have shown waning of the growth response (Rochiccioli et al, 1987) on once-daily injection.…”
Section: Discussionsupporting
confidence: 68%
“…In spite of several short-term positive results, clinical trials of longer duration have shown that these agents did not increase growth or adult height. More recently, short-term clinical trials with GHRH or GHreleasing peptides (GHRPs) have been performed, which appear to have led to some increase of height velocity [127][128][129][130]. However, no long-term results have been reported.…”
Section: Other Pharmaceutical Agentsmentioning
confidence: 99%
“…In conclusion, and in spite of the fact that the effects demonstrated in this study are only acute, it is tempting to speculate that the combination of clonidine (one or two daily doses, orally) and G R F (slow-releasing forms) may result in a useful new treatment for hypothalamic GH-deficient children. Potential benefits expected to occur would be (1) the establishment of a more physiological pulsatile pattern of G H secretion, which would imply better growth-promoting effects (Clark et al, 1985); and (2) the avoidance of a time and dose-dependent increased somatostatinergic tone blunting the secretion of GH (Hernandez et al, 1988).…”
Section: Dlscurslonmentioning
confidence: 99%